Large-scale genome editing in plants: approaches, applications, and future perspectives. (February 2023) - Liu, Tianzhen; Zhang, Xuening; Li, Kai; Yao, Qi; Zhong, Dating; Deng, Qi; Lu, Yuming
Abstract : As a powerful genome editing technology, CRISPR/Cas is revolutionizing both fundamental research and crop breeding, and has now evolved into large-scale editing tools that are efficient, simple, and programmable. With such CRISPR screening technologies, the numbers of genome-edited crops are rapidly increasing. Here, we describe the general workflow of a CRISPR screen in plants, including the selection of appropriate editors, genome-wide guide RNA design, pooled library construction, massive transformation, and high-throughput genotyping. We also discuss applications for the screening of candidate genes, the optimization of spatiotemporal expression, the evolution of protein activities, and the establishment of genome-wide libraries of knockout mutant. After considering the current challenges and limitations, we finally envision a virus-mediated strategy to improve CRISPR screens. Highlights: Presented the typical workflow of a CRISPR screen in plants. Collected and described appropriate genome editors for large-scale editing in plant. Envisioned a virus-mediated plant CRISPR screens.